Direct and rapid quantitation of ephedrines in human urine by paper spray ionization/high resolution mass spectrometry - Jeong, Eun Sook; Kim, Ki Hun; Cha, Eunju; Kwon, Oh-Seung; Cha, Sangwon; Lee, Jaeick (ELSEVIER SCIENCE BV, 2016)
A rapid and direct paper spray ionization/mass spectrometry (PSI/MS) method was developed for quantitative analysis of ephedrine, pseudoephedrine, norpseudoephedrine, and methylephedrine in human urine. This method involves the use of a triangular filter paper and high-resolution mass spectrometry, where the molecular ions of ephedrines were generated by applying high voltage after loading the spray solvent to the paper which urine sample was pre-loaded. Small amounts (2 mu L) of urine spiked with an internal standard were directly analyzed for ephedrines. The PSI/MS method was validated for linearity, within- and between-run precision, accuracy, and limit of detection. The results showed good linearity (R-2 >= 0.9928) and acceptable precision and accuracy. Furthermore, the accuracy of the method was assessed by analyzing a blind urine sample from World Anti-Doping Agency and comparing the measured concentrations with the nominal concentrations. This test resulted in accuracies ranging from 96.4 to 106.1%, indicating that the PSI/MS method has the potential to be an alternative technique for the fast quantitation of ephedrines in doping control analysis. (C) 2016 Elsevier B.V. All rights reserved.